Face Mask as Veil: Social Identity and Negotiation among Female Students in Indonesian Islamic University - Tubangsa, Ian; Anggriani Syarif, Selvy (Prodi Sosiologi Universitas Mataram, 2024)
After the pandemic ended, face masks were still widely used by students in Islamic universities, especially by veiled female students. This article aims to understand the social identity construction of the group of female students wearing face masks as veil and how they seek to negotiate veils to avoid discrimination. The research uses phenomenology method, with purposive sampling. Data collection was carried out by in-depth interviews with 30 informants who had been observed for three months. The result show how veiled female students formed their social identities through Tajfel’s social identity theory. The veiled female students tend to positively assess the wear of the niqab as strengthening the in-group and increasing their self-esteem as devout Muslim women. To respected and get affirmatively valued, female students negotiating of wearing face masks as niqab, become open personalities, pursue academic achievements, and appear as a fashionable Muslimah.